Rurality and social work: a perspective from Andalusia - González-Portillo, Auxiliadora; Ruiz-Ballesteros, Esteban (Cuadernos de Trabajo Social, 2023)
Social work in rural areas, in contrast to its configuration in urban settings, is conditioned by particular organisational circumstances and socio-cultural contexts that call for reflection on its possible specificity. In this sense, the practice of social work in rural contexts is a specific challenge for the profession. The aim of this article is to analyse the organisational models and practice of social work in a rural context in order to investigate this potential particularity and its implications for social intervention. The research focuses on an exploratory case study in Andalusia (Spain), where we have developed a qualitative research in 14 community social services centres through in-depth interviews with 95 social workers. Through these interviews we have been able to identify some of the characteristics of the organisation and practices of social workers in rural contexts. The results highlight two fundamental differences with intervention in urban contexts: (1) a different model of service organisation, with a generalist tendency; and (2) a particular professional practice, based on personal proximity and care. In the discussion section, the particularities of rural social work is highlighted: the professionals recognise that they are doing social work that is "different" from that in urban contexts, more aligned with the profession "ought" and "is". The conclusions point to the existence of an urbanormativity bias in the organisation and practices of social work which makes rural peculiarities invisible and which could condition its capacity to respond to the rural crisis.